Process for the catalytic synthesis of high molecular weight polyisobutylene and its weakly coordinated anion salt / alkylaluminum complex system

CN122878481APending Publication Date: 2026-10-09DALIAN UNIV OF TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611383994.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0013]本发明的目的在于,用于克服现有技术中采用传统强Lewis酸体系引发异丁烯阳离子聚合时,存在聚合温度低、设备腐蚀严重、催化体系稳定性差、链转移副反应较多以及难以兼顾高分子量、高转化率和较窄分子量分布等技术问题,提供一种高分子量聚异丁烯及其弱配位阴离子盐/烷基铝复合体系催化合成方法

Benefits of technology

(1)本发明采用弱配位阴离子与混合烷基铝构建复合引发体系,相比传统单一Lewis酸体系,能够提高碳正离子活性中心的稳定性,降低聚合过程中链转移及链终止副反应,提高聚合可控性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878481A_ABST
    Figure CN122878481A_ABST
Patent Text Reader

Abstract

The application relates to a high-molecular-weight polyisobutene and a catalytic synthesis method of a weakly coordinated anion salt / alkyl aluminum composite system, and belongs to the field of high-molecular-weight compound preparation. In the application, isobutene is used as a polymerization monomer, a weakly coordinated anion compound and alkyl aluminum are used to form a composite initiation system, and a cationic polymerization reaction is carried out under low-temperature conditions of-90 DEG C to-30 DEG C. The weakly coordinated anion compound has weak nucleophilicity and low coordination ability, is introduced in the form of an organic salt such as an iodonium salt and a triaryl carbonium salt, and is cooperated with alkyl aluminum to construct a cationic polymerization active center with high activity and high stability. The method has the characteristics of stable and controllable polymerization reaction and high monomer conversion rate, can efficiently induce active / controllable cationic polymerization of isobutene in a wide temperature range, and the weight-average molecular weight of the obtained polyisobutene product is up to 157.9*10 4 g / mol, and the molecular weight distribution index is narrow.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer compound preparation, specifically relating to a catalytic synthesis method for high molecular weight polyisobutylene and its weakly coordinated anionic salt / alkyl aluminum composite system. Background Technology

[0002] Polyisobutylene (PIB) is an important class of saturated polyolefin materials with excellent resistance to heat and oxygen aging, ozone, and acid and alkali corrosion, as well as good gas tightness, electrical insulation, and chemical stability. It is widely used in tire inner linings, sealing materials, damping materials, lubricant additives, adhesives, medical materials, and aerospace applications. Based on the polymer molecular weight, PIB is generally classified into low molecular weight PIB, medium molecular weight PIB, and high molecular weight PIB (HMPIB). Among these, high molecular weight PIB, due to its higher molecular chain entanglement density, exhibits superior mechanical properties, fatigue resistance, creep resistance, and gas barrier properties, making it a crucial base resin for the preparation of high-performance elastomer materials.

[0003] Polyisobutylene is typically prepared using cationic polymerization. Due to the high electron cloud density of isobutylene molecules, carbocation active centers can be rapidly formed in the presence of Lewis acids, resulting in fast polymerization rates and high reactivity. However, the active centers exhibit poor stability during cationic polymerization, making them prone to side reactions such as monomer chain transfer, solvent chain transfer, and chain termination. These side reactions cause a rapid decrease in polymer molecular weight and a broadening of the molecular weight distribution, severely impacting product performance. Therefore, the preparation of high molecular weight polyisobutylene has always been an important research area in the field of cationic polymerization.

[0004] Currently, the industrial production of high molecular weight polyisobutylene mainly employs strong Lewis acids such as aluminum trichloride, boron trifluoride, boron chloride, and titanium tetrachloride as co-initiators, combined with water, alcohols, organohalides, or ethers to form a two-component initiation system. This system can rapidly generate carbocation active centers, achieving isobutylene polymerization at extremely low temperatures and yielding polymers with high molecular weights. However, this type of system generally suffers from problems such as the strong corrosiveness of Lewis acids, high equipment maintenance costs, low polymerization temperatures, and high energy consumption. In particular, most industrial production processes need to be carried out at temperatures around -100 °C or even lower to suppress chain transfer reactions and improve the lifetime of active centers. This not only increases investment in refrigeration systems but also raises production operating costs, limiting the large-scale, low-cost production of high molecular weight polyisobutylene.

[0005] In recent years, to reduce the influence of polymerization temperature on polymerization behavior, researchers have conducted extensive studies on co-initiator structure design, electron donor regulation, mixed Lewis acid systems, novel initiators, and continuous polymerization processes. For example, by using alkyl aluminum chloride instead of traditional aluminum trichloride, the acidity of Lewis acids can be appropriately reduced, and the binding ability of anti-anions to carbocations can be improved, thereby improving polymerization controllability. Using electron donors such as ethers and esters to form coordination structures with Lewis acids can further stabilize the active center and reduce chain transfer reactions. Mixed Lewis acid systems, by adjusting the ratio between different Lewis acids, can maintain initiation activity while taking into account ion pair stability, giving the polymerization system a certain wide-temperature-range polymerization capability.

[0006] While the aforementioned studies have improved polymerization performance to some extent, they still fundamentally rely on the tight ion pairs formed by traditional halo-Lewis acids for regulation. When the Lewis acid is too strong, although it can rapidly initiate polymerization, it easily leads to an overly tight bond between the anti-anion and the growing chain, increasing chain termination and chain transfer reactions. Conversely, when the Lewis acid acid is weaker, the initiation efficiency may decrease, slowing down the polymerization rate and making it difficult to simultaneously achieve high molecular weight, high conversion rate, and a narrow molecular weight distribution. Therefore, how to further regulate the interaction between the carbocation and anti-anion, improve the stability of the active center, and maintain high polymerization activity remains a crucial problem to be solved in the preparation of high molecular weight polyisobutylene.

[0007] Weakly coordinating anions (WCAs) have attracted widespread attention in organic cationic chemistry, homogeneous catalysis, and cationic polymerization due to their characteristics of high charge delocalization, large steric volume, weak nucleophilicity, and low coordination ability. WCAs can effectively reduce the interaction between anions and cations, maintaining the high activity of the cation while preventing the anion from directly participating in side reactions. Therefore, they are widely used in organometallic catalysis, olefin polymerization, and the construction of active cationic systems. Among them, weakly coordinating anion systems, represented by tetra(pentafluorophenyl)borate, perfluoroborate, and their derivatives, possess significant steric hindrance and low nucleophilicity, enabling them to maintain cation activity while improving ion pair stability, thus providing a new research direction for highly active cationic polymerization.

[0008] Currently, weakly coordinating anions are mainly used in metallocene catalysts, rare earth catalysts and other metal coordination polymerization systems, and there is relatively little research on their application in the cationic polymerization of isobutylene.

[0009] Barsan et al. reported the preparation of highly active polyisobutylene using a monotitanium / weakly coordinated boron anion system (Macromolecules, 1998, 31(24), 8439-8447), through the in-situ generation of cationic titanium active centers [CpTiMe2] via CpTiMe and B(CF). + [MeB(C6F5)3] - This method utilizes weakly coordinated boron anions to reduce the interaction between counterions and terminal carbocations of active chains, thereby enhancing carbocation stability and promoting the growth of isobutylene cationic chains to obtain polyisobutylene. However, the monotitanium compounds and fluorinated boron anion systems used in this method are complex to synthesize and costly, and the catalytic system has strict requirements for the polymerization environment, which is not conducive to industrial-scale promotion.

[0010] Patent publication EP1344785A1 employs an improved cationic polymerization process and reaction system to prepare polyisobutylene. It optimizes the initiation system, polymerization conditions, and reaction medium by introducing a combination of a weakly coordinating anion (nickel / manganese compound) and an alkyl nitrile ligand, thereby improving the polymerization reactivity and process stability, and to some extent, enhancing the molecular weight and distribution of polyisobutylene. However, this method still requires strict control of polymerization conditions and has limited stabilizing effect on the active sites in the polymerization system.

[0011] On the other hand, alkylaluminum compounds possess advantages such as moderate Lewis acid strength, abundant sources, low cost, and relatively low corrosivity, making them promising candidates for polyolefin polymerization and cationic polymerization. Significant differences in Lewis acid strength exist between alkylaluminum compounds with different structures. By combining different types of alkylaluminum compounds, the overall Lewis acidity of the system can be further adjusted, providing a suitable reaction environment for the stable existence of weakly coordinating anions. Therefore, constructing novel initiation systems by combining weakly coordinating anions with mixed alkylaluminum compounds holds promise for achieving a more stable dynamic balance between the carbocation active center and the weakly coordinating anion while ensuring initiation activity. This would further suppress chain transfer and chain termination reactions, improve the catalytic performance of the polymerization system over a wider temperature range, and yield polyisobutylene products with high molecular weight, high conversion rate, and narrow molecular weight distribution.

[0012] However, research on the synergistic mechanism of weakly coordinating anions and mixed alkyl aluminum and their application in the preparation of high molecular weight polyisobutylene remains limited. In particular, systematic studies are lacking regarding the screening of weakly coordinating anions, the control of mixed alkyl aluminum composition, the matching of their ratios, and their polymerization behavior over a wide temperature range. Existing technologies still struggle to simultaneously meet the requirements of high molecular weight, high conversion rate, a wide operating temperature range, and low equipment corrosion. Therefore, developing a composite initiation system constructed from weakly coordinating anions and mixed alkyl aluminum to achieve efficient and controllable polymerization of isobutylene over a wide temperature range is of great significance for reducing polymerization energy consumption, improving the stability of the catalytic system, increasing the efficiency of high molecular weight polyisobutylene preparation, and promoting its industrial application. Summary of the Invention

[0013] The purpose of this invention is to overcome the technical problems in the existing technology of using traditional strong Lewis acid systems to initiate the cationic polymerization of isobutylene, such as low polymerization temperature, severe equipment corrosion, poor stability of the catalytic system, many chain transfer side reactions, and difficulty in achieving high molecular weight, high conversion rate and narrow molecular weight distribution. The invention provides a catalytic synthesis method for high molecular weight polyisobutylene and its weakly coordinated anionic salt / alkyl aluminum composite system.

[0014] The present invention provides a weakly coordinating anionic salt / alkylaluminum composite system suitable for cationic polymerization of isobutylene under a wide temperature range. By utilizing the low coordination ability and large steric hindrance of the weakly coordinating anionic compound, and combining the synergistic effect between alkylaluminates with different Lewis acid strengths, the system can improve the stability of the activated carbocation while ensuring initiation efficiency, and reduce chain transfer and chain termination side reactions during polymerization, thereby achieving the efficient preparation of high molecular weight polyisobutylene.

[0015] To achieve the above objectives, the present invention adopts the following technical solution.

[0016] This invention provides a method for the catalytic synthesis of high molecular weight polyisobutylene using a weakly coordinating anionic salt / alkyl aluminum composite system. Isobutylene is used as the polymerization monomer, and a weakly coordinating anionic compound and alkyl aluminum are used as the composite initiation system. The cationic polymerization reaction is carried out under low temperature conditions. After the polymerization is completed, the reaction is terminated, and high molecular weight polyisobutylene is obtained by precipitation, washing and drying.

[0017] Among them, the weakly coordinating anionic compound is selected from organic anionic systems with weak nucleophilicity, low coordination ability and large steric hindrance. The weakly coordinating anion is selected from one or more of tetra(pentafluorophenyl)borate, tetra[3,5-bis(trifluoromethyl)phenyl]borate, perfluoroalkoxyaluminate and their derived anions.

[0018] The weakly coordinating anion is added to the polymerization system in the form of an iodonium salt, a caronium salt, or an organic salt capable of forming a stable carbocation. The iodonium salt is selected from one or more of diaryliodonium salts and iodonium salts containing a weakly coordinating anion. The caronium salt is selected from one or more of triphenylcaronium salts, tri(methylphenyl)caronium salts, and triarylcaronium salts containing a weakly coordinating anion. The organic salt capable of forming a stable carbocation is selected from one or more of N,N-dimethylaniline ononium salt, sodium tetra(pentafluorophenyl)borate, and sodium tetra[3,5-bis(trifluoromethyl)phenyl]borate.

[0019] The alkyl aluminum is selected from one or more of dichloroethylaluminum, diethylaluminum chloride, diisobutylaluminum chloride, dimethylaluminum chloride, and other alkyl aluminum compounds with Lewis acidity; preferably, two or more alkyl aluminum compounds are used; wherein, when using diethylaluminum chloride, at least two alkyl aluminum compounds are mixed.

[0020] The method for catalytic synthesis of high molecular weight polyisobutylene using a weakly coordinated anionic salt / alkyl aluminum composite system of the present invention further includes the following steps: S1: Material preparation: The polymerization reaction system is an anhydrous and oxygen-free inert gas environment. The solvent, monomer, weakly coordinated anionic compound, and alkyl aluminum are all stored in an inert environment after being dehydrated and deoxygenated. S2: Aggregation: A weakly coordinating anionic compound was added to a low-temperature isothermal reactor to replace the reactor with an anhydrous and oxygen-free inert gas environment. Solvent and monomer were added, and the polymerization system was obtained at the equilibrium temperature of the low-temperature isothermal reactor. Alkyl aluminum was added to initiate the reaction and polymerization was carried out. After the polymerization was completed, a terminator was added to terminate the reaction and obtain the polymerization product. S3: Post-processing: After removing unreacted monomers and solvents from the polymerization product, it was treated with ethanol immersion and then vacuum dried to obtain high molecular weight polyisobutylene.

[0021] In S1, the solvent is selected from one or more of chloromethane, dichloromethane, n-hexane, toluene, chlorobenzene, and their mixed solvents.

[0022] In S1, the inert gas is selected as nitrogen or argon.

[0023] In S2, the inert gas is either nitrogen or argon.

[0024] In S2, the polymerization temperature is -90 ℃ to -30 ℃.

[0025] In S2, when there is only one type of alkyl aluminum, it is added to the polymerization system by slow dropwise addition at a rate of 0.5 to 2 mL / min; when there are two or more types of mixed alkyl aluminum, the alkyl aluminum is first mixed and then added to the initiation system at a rate of 0.5 to 2 mL / min.

[0026] The molar ratio of the weakly coordinated anionic compound to alkyl aluminum is 1:10 to 1:100.

[0027] The polymerization system uses a weakly coordinating anionic compound and alkyl aluminum as a composite initiation system, and the total concentration of the composite initiation system in the polymerization system is 10–100 mmol / L.

[0028] The isobutylene monomer accounts for 5 wt% to 50 wt% of the polymerization system.

[0029] The polymerization time is 1 to 60 minutes.

[0030] In S2, the time for equilibration at the low-temperature constant temperature reactor is preferably 15-30 minutes.

[0031] In S3, the terminator is selected from water, anhydrous methanol, anhydrous ethanol, or an ethanol / water mixed solution containing 1 wt% NaOH; in the ethanol / water mixed solution, the volume ratio of ethanol to water is 1:1; the amount of terminator accounts for 1 to 5% of the volume percentage of the polymerization system.

[0032] In step S3, the method for removing unreacted monomers and solvents is vacuum evaporation.

[0033] In S3, the ethanol soaking time is more than 12 hours.

[0034] In S3, the vacuum drying process parameters are: pressure -0.1 MPa, drying at 40~50 ℃ to constant weight.

[0035] The high molecular weight polyisobutylene of this invention, prepared by the above method, has a molecular weight of 76.5 × 10⁻⁶. 4 ~157.9×10 4 g / mol, monomer conversion rate reaches 65% to 99%, molecular weight distribution is 1.99 to 5.60.

[0036] This invention employs a composite initiation system synergistically constructed from weakly coordinating anions and alkylaluminum, particularly mixed alkylaluminum. By adjusting the ratio of different Lewis acids, the onium salt is effectively activated to form a carbocation active center, while avoiding excessive coordination or deactivation of the weakly coordinating anion due to over-strength of the Lewis acid. In the composite initiation system, a stable ion-pair structure is formed between the weakly coordinating anion and the carbocation, maintaining a dynamic balance between the active center and dormant species, improving the stability of the polymerization system, reducing chain transfer and chain termination reactions, and increasing the polymerization efficiency of isobutylene.

[0037] This invention optimizes the overall performance of the polymerization system by adjusting the type of weakly coordinating anionic compound, alkyl aluminum, especially the mixed alkyl aluminum composition, the ratio of weakly coordinating anionic compound and alkyl aluminum, polymerization temperature, solvent composition, monomer concentration and polymerization time, resulting in polyisobutylene with higher molecular weight, higher monomer conversion rate and narrower molecular weight distribution.

[0038] The present invention has the following beneficial effects: (1) The present invention uses a weakly coordinated anion and a mixed alkyl aluminum to construct a composite initiation system. Compared with the traditional single Lewis acid system, it can improve the stability of the carbocation active center, reduce chain transfer and chain termination side reactions during polymerization, and improve the controllability of polymerization.

[0039] (2) This invention utilizes the synergistic effect between alkyl aluminums with different Lewis acid strengths to achieve a match between initiation ability and ion pair stability, which is beneficial to improve the catalytic activity of the polymerization system and maintain the continuous growth of active centers.

[0040] (3) By screening the weakly coordinated anion structure, the type of alkyl aluminum and the ratio of the two, the present invention establishes a composite initiation system suitable for the cationic polymerization of isobutylene. It can maintain high polymerization activity in a wide range of polymerization temperature and effectively reduce the dependence of the polymerization process on extremely low temperature conditions.

[0041] (4) The method provided by this invention can prepare high molecular weight polyisobutylene, and the polymerization system has high monomer conversion rate, high weight-average molecular weight, and good molecular weight distribution. Under optimized conditions, this system can achieve efficient polymerization in a wide temperature range of -90 ℃ to -30 ℃, with a maximum monomer conversion rate of about 92% and a polymer weight-average molecular weight of about 157.9 × 10⁻⁶. 4 The formula has a molecular weight distribution of 2.38 g / mol and can stably prepare high molecular weight polyisobutylene at -30 °C. Attached Figure Description

[0042] Figure 1 The graphs show the GPC test curves of the high molecular weight polyisobutylene prepared in Examples 1, 2, and 3. Detailed Implementation

[0043] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and technical solutions.

[0044] The following examples illustrate the preparation method of high molecular weight polyisobutylene: Pre-experimental treatment: The polymerization reaction was carried out under nitrogen or argon atmosphere. Double-row tubes were used to ensure the inert environment of the reaction system. The solvent and isobutylene (IB) monomer were dehydrated and deoxygenated under certain conditions, and were stored in an inert environment along with weakly coordinating anionic salts (WCAs) and co-initiators to strictly ensure that the system was anhydrous and oxygen-free.

[0045] The solvent used is one or a mixture of hexane, tetrahydrofuran, chloromethane, dichloromethane, toluene, chloroethane, vinyl chloride, and propane.

[0046] The general procedure for polymerization is as follows: First, a certain amount of weakly coordinated anionic salts (WCAs) is added to the Schlenk reaction tube. The double-row tube is then connected, and after three purgings, the tube is placed in a low-temperature isothermal reactor. With a sufficiently high inert gas flow rate, the solvent and monomer are sequentially added to the reaction tube using a syringe or feed vessel equipped with a long needle that has been purged with inert gas three times. The temperature is then equilibrated for 20 minutes. One or two co-initiators are added using a specific method to initiate the reaction. The reaction is terminated by adding a terminator after the set polymerization time has been reached.

[0047] The inert environment is nitrogen or argon.

[0048] The concentration of the isobutylene (IB) monomer is 5wt% to 50wt%.

[0049] The molar ratio of the weakly coordinating anionic salt (WCAs) to alkyl aluminum is 1: (10-100).

[0050] The alkylaluminum content of the monomer is 0.02–10 wt%.

[0051] The polymerization time is 1 to 60 minutes.

[0052] The co-initiator is added in the following manner: one co-initiator is added slowly and directly, and two co-initiators are added sequentially with an interval of 0-45 minutes.

[0053] The temperature setting of the low-temperature constant temperature reactor is -60℃ to -90℃.

[0054] The terminator is one of the following: water, anhydrous methanol, anhydrous ethanol, or a mixed solution of ethanol / water (V / V=1) containing 1wt% NaOH. The amount of terminator used is generally 1-5% (V / V) of the polymerization system.

[0055] The general post-processing procedure is as follows: After removing unreacted monomers and solvents by vacuum evaporation of the polymerized product, the product is washed and soaked in ethanol for 12 h. The product is then dried to constant weight under a pressure of -0.1 MPa and a temperature of 40 °C. The yield is calculated, and the molecular weight and distribution index are determined by gel permeation chromatography (GPC).

[0056] The yield calculation method in this embodiment of the invention is as follows: the yield calculation adopts the weighing method. Yield (%) = mass of PIB polymer (g) / mass of IB monomer (g).

[0057] The molecular weight of this invention was determined using the GPC method: the GPC calibrator was polystyrene (PS), and the solvent was tetrahydrofuran (THF). The polymer sample was prepared as a solution with a concentration of 1 mg / mL. Measurements were performed at a flow rate of 1 mL / min and a column temperature of 35 °C to obtain the average molecular weight and molecular weight distribution index (PDI) data. The PDI is defined as: PDI = weight-average molecular weight (Mw) / number-average molecular weight (Mn) of the polymer product.

[0058] Example 1

[0059] Under nitrogen protection at -90 °C, 10 μmol of a weakly coordinated anionic salt, diaryliodonium tetra(pentafluorophenyl)borate ((4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate), 2 g of isobutylene (IB), 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, 0.1 mL of a 25 wt% dichloroethylaluminum n-hexane solution (containing 0.128 mmol of dichloroethylaluminum) was added to initiate the reaction. After stirring for 30 min, 2 mL of anhydrous ethanol was added to terminate the reaction. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 99%. GPC testing was performed, and the curve is shown in the figure. Figure 1 It is a high molecular weight polyisobutylene with a unimodal distribution. Mw = 88.1 × 10 4 g / mol, Mn=16.6×10 4 g / mol, molecular weight distribution index (PDI) is 5.36.

[0060] Example 2

[0061] Under nitrogen protection at -90 °C, 10 μmol of a weakly coordinated anionic salt, diaryliodonium tetra(pentafluorophenyl)borate ((4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate), 2 g of isobutylene, 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, a 1:1 mixture of dichloroethylaluminum and diethylaluminum chloride (containing 0.128 mmol of dichloroethylaluminum and 0.128 mmol of diethylaluminum chloride) was added to initiate the reaction. After stirring for 30 min, 2 mL of anhydrous ethanol was added to terminate the reaction. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 92%. GPC analysis was performed, and the curve is shown in the figure. Figure 1 It is a high molecular weight polyisobutylene with a unimodal distribution. Mw = 157.9 × 10 4 g / mol, Mn=66.3×10 4 g / mol, PDI=2.38.

[0062] Example 3

[0063] Under nitrogen protection at -90 °C, 10 μmol of a weakly coordinated anionic salt, diaryliodonium tetra(pentafluorophenyl)borate ((4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate), 2 g of isobutylene, 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, a 2:1 mixture of dichloroethylaluminum and diethylaluminum chloride (containing 0.171 mmol of dichloroethylaluminum and 0.085 mmol of diethylaluminum chloride) was added to initiate the reaction. After stirring for 30 min, 2 mL of anhydrous ethanol was added to terminate the reaction. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 92%. GPC analysis was performed, and the curve is shown in the figure. Figure 1 It is a high molecular weight polyisobutylene with a unimodal distribution. Mw = 122.1 × 10 4 g / mol, Mn=22.1×10 4 g / mol, PDI=5.53.

[0064] Example 4

[0065] Under nitrogen protection at -90 °C, 10 μmol of the weakly coordinated anionic salt sodium tetra(pentafluorophenyl)borate, 2 g of isobutylene, 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, a 1:1 mixture of dichloroethylaluminum and diethylaluminum chloride (containing 0.128 mmol of dichloroethylaluminum and 0.128 mmol of diethylaluminum chloride) was added to initiate the reaction. After stirring for 30 min, 2 mL of anhydrous ethanol was added to terminate the reaction. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 65%. GPC analysis showed that it was a high molecular weight polyisobutylene with a unimodal distribution. Mw = 135.9 × 10⁻⁶ 4 g / mol, Mn=47.0×10 4 g / mol, PDI=2.89.

[0066] Example 5

[0067] Under nitrogen protection at -90 °C, 10 μmol of the weakly coordinating anionic salt sodium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate, 2 g isobutylene, 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, a 1:1 mixture of dichloroethylaluminum and diethylaluminum chloride (containing 0.128 mmol of dichloroethylaluminum and 0.128 mmol of diethylaluminum chloride) was added to initiate the reaction. After stirring for 30 min, 2 mL of anhydrous ethanol was added to terminate the reaction. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 87%. GPC analysis showed that it was a high molecular weight polyisobutylene with a unimodal distribution. Mw = 135.6 × 10⁻⁶ 4 g / mol, Mn=42.9×10 4 g / mol, PDI=3.16.

[0068] Example 6

[0069] Under nitrogen protection at -90 °C, 10 μmol of the weakly coordinated anionic salt N,N-dimethylaniline-onium tetra(pentafluorophenyl)borate, 2 g of isobutylene, 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, a 1:1 mixture of dichloroethylaluminum and diethylaluminum chloride (containing 0.128 mmol of dichloroethylaluminum and 0.128 mmol of diethylaluminum chloride) was added to initiate the reaction. After stirring for 30 min, the reaction was terminated by adding 2 mL of anhydrous ethanol. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 71%. GPC analysis showed that it was a high molecular weight polyisobutylene with a unimodal distribution. Mw = 110.3 × 10⁻⁶ 4 g / mol, Mn=21.7×10 4 g / mol, PDI=5.08.

[0070] Example 7

[0071] The difference between Example 7 and Example 2 is that in Example 7, the solvent is dichloromethane:n-hexane in a volume ratio of 2:6 instead of 6:2 (dichloromethane:n-hexane = 6:2), while all other parameters remain unchanged. The calculated yield is 93%. GPC testing showed it to be a single-peaked high molecular weight polyisobutylene. Mw = 128.3 × 10⁻⁶ 4 g / mol, Mn=58.8×10 4 g / mol, PDI=2.18.

[0072] Example 8

[0073] Under nitrogen protection at -90 °C, 10 μmol of the weakly coordinating anionic salt triphenylmethyltetra(pentafluorophenyl)borate, 2 g isobutylene, 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, 0.1 mL of a 25 wt% dichloroethylaluminum n-hexane solution (containing 0.128 mmol of dichloroethylaluminum) was added to initiate the reaction. After stirring for 30 min, 2 mL of anhydrous ethanol was added to terminate the reaction. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 98%. GPC analysis showed that it was a high molecular weight polyisobutylene with a unimodal distribution. Mw = 99.7 × 10⁻⁶ 4 g / mol, Mn=17.8×10 4 g / mol, PDI=5.60.

[0074] Example 9

[0075] Under nitrogen protection at -90 °C, 10 μmol of the weakly coordinating anionic salt triphenylmethyltetra(pentafluorophenyl)borate, 2 g isobutylene, 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, 0.064 mL of a 2.0 mol / L diethylaluminum chloride n-hexane solution (containing 0.128 mmol of diethylaluminum chloride) was added to initiate the reaction. After stirring for 30 min, 2 mL of anhydrous ethanol was added to terminate the reaction. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 87%. GPC analysis showed that it was a high molecular weight polyisobutylene with a unimodal distribution. Mw = 83.3 × 10⁻⁶ 4 g / mol, Mn=29.8×10 4 g / mol, PDI=2.79.

[0076] Example 10

[0077] The difference between Example 10 and Example 2 is that the polymerization temperature in Example 10 was changed from -90℃ to -30℃, and the calculated yield was 83%. GPC testing showed it to be a high molecular weight polyisobutylene with a unimodal distribution. Mw = 76.5 × 10⁻⁶ 4 g / mol, Mn=38.4×10 4 g / mol, PDI=1.99.

[0078] Example 11

[0079] Under nitrogen protection at -90 °C, 10 μmol of the weakly coordinated anionic salt (4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate, 2 g isobutylene, 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, a 1:1 mixture of dichloroethylaluminum and diisobutylaluminum chloride (containing 0.128 mmol of dichloroethylaluminum and 0.128 mmol of diisobutylaluminum chloride) was added to initiate the reaction. After stirring for 30 min, 2 mL of anhydrous ethanol was added to terminate the reaction. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 84%. GPC analysis showed that it was a high molecular weight polyisobutylene with a unimodal distribution. Mw = 131.7 × 10⁻⁶ 4 g / mol, Mn=51.4×10 4 g / mol, PDI=2.56.

[0080] Example 12

[0081] Under nitrogen protection at -90 °C, 10 μmol of the weakly coordinating anionic salt (4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate, 6 g of isobutylene, 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, a 1:1 mixture of dichloroethylaluminum and dimethylaluminum chloride (containing 0.128 mmol of dichloroethylaluminum and 0.128 mmol of dimethylaluminum chloride) was added to initiate the reaction. After stirring for 30 min, 2 mL of anhydrous ethanol was added to terminate the reaction. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 76%. GPC analysis showed that it was a high molecular weight polyisobutylene with a unimodal distribution. Mw = 144.3 × 10⁻⁶. 4 g / mol, Mn=55.9×10 4 g / mol, PDI=2.58.

[0082] Example 13

[0083] The difference between Example 13 and Example 2 is that in Example 13, the monomer mass was changed from 2g to 0.5g, and the calculated yield was 98%. GPC testing showed it to be a high molecular weight polyisobutylene with a unimodal distribution. Mw = 114.5 × 10⁻⁶. 4 g / mol, Mn=51.9×10 4 g / mol, PDI=2.20.

[0084] Example 14

[0085] The difference between Example 14 and Example 2 is that the polymerization time in Example 14 was 60 min instead of 30 min, and the calculated yield was 93%. GPC testing showed it to be a unimodal high molecular weight polyisobutylene. Mw = 151.8 × 10⁻⁶ 4 g / mol, Mn=64.7×10 4 g / mol, PDI=2.35.

[0086] Example 15

[0087] The difference between Example 15 and Example 2 is that in Example 15, 30 μmol of (4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate was used instead of 10 μmol, with a calculated yield of 91%. GPC testing showed it to be a high molecular weight polyisobutylene with a single-peak distribution. Mw = 97.3 × 10⁻⁶ 4 g / mol, Mn=29.1×10 4 g / mol, PDI=3.32.

[0088] Example 16

[0089] The difference between Example 16 and Example 2 is that in Example 16, 5 μmol of (4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate was used instead of 10 μmol, with a calculated yield of 88%. GPC testing showed it to be a high molecular weight polyisobutylene with a single-peak distribution. Mw = 111.9 × 10⁻⁶ 4 g / mol, Mn=50.1×10 4 g / mol, PDI=2.23.

[0090] Example 17

[0091] The difference between Example 17 and Example 2 is that in Example 17, the content of mixed alkyl aluminum was replaced by 0.328 mL instead of 0.164 mL (resulting in 0.256 mmol of dichloroethylaluminum and 0.256 mmol of diethylaluminum chloride), with a calculated yield of 91%. GPC testing showed it to be a unimodal high molecular weight polyisobutylene. Mw = 107.3 × 10⁻⁶ 4 g / mol, Mn=39.1×10 4 g / mol, PDI=2.74.

[0092] Example 18

[0093] Under nitrogen protection at -90 °C, 10 μmol of the weakly coordinated anionic salt lithium tetrakis(perfluorotert-butoxy)aluminate, 2 g of isobutylene, 6 mL of dichloromethane, and 2 mL of n-hexane were sequentially transferred into a Schlenk tube. After magnetic stirring for 20 min, a 1:1 mixture of dichloroethylaluminum and diethylaluminum chloride (containing 0.128 mmol of dichloroethylaluminum and 0.128 mmol of diethylaluminum chloride) was added to initiate the reaction. After stirring for 30 min, 2 mL of anhydrous ethanol was added to terminate the reaction. The polymerized product was obtained, and after removing unreacted monomers and solvent, it was dried. The yield was calculated to be 79%. GPC analysis showed that it was a high molecular weight polyisobutylene with a unimodal distribution. Mw = 88.2 × 10⁻⁶ 4 g / mol, Mn=31.8×10 4 g / mol, PDI=2.77.

[0094] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 did not contain dichloroethylaluminum, and the experimental result was no product.

[0095] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that Lewis acid in Comparative Example 2 was replaced with diethylaluminum chloride. The experimental results showed a conversion rate of 7%, which was too low. This indicates that the Lewis acidity of diethylaluminum chloride is relatively weak, and using this Lewis acid alone is usually not effective.

[0096] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 only added dichloroethylaluminum and did not add a weakly coordinating anionic salt. The calculated yield was 39%, and the yield was 42.9 × 10⁻⁶ using GPC testing. 4 g / mol, Mn=2.08×10 4 The PDI is 20.6 g / mol because dichloroethylaluminum has a strong Lewis acid content, which can cause very small amounts of water in the system to be released. However, the PDI is too wide, making the system uncontrollable.

[0097] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 used tris(pentafluorophenyl)boron instead of (4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate, with a calculated yield of 51%; GPC testing showed it to be a high molecular weight polyisobutylene with a single-peak distribution. Mw = 82.9 × 10⁻⁶ 4 g / mol, Mn=9.4×10 4 The g / mol and PDI=8.93 indicate that only weakly coordinated anionic salts can produce high molecular weight polyisobutylene. Tris(pentafluorophenyl)boron is electroneutrally neutral and does not belong to the category of weakly coordinated anionic salts.

[0098] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that Comparative Example 5 uses tris(pentafluorophenyl)boron instead of (4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate, with a calculated yield of 99%; GPC testing showed it to be a high molecular weight polyisobutylene with a unimodal distribution. Mw = 56.3 × 10⁻⁶ 4 g / mol, Mn=31.4×10 4 g / mol, PDI=1.79, the PDI is very low, but the molecular weight is too low, indicating that only a weakly coordinating anionic salt can obtain high molecular weight polyisobutylene. Tris(pentafluorophenyl)boron is electrically neutral and does not belong to the category of weakly coordinating anionic salts.

[0099] Comparative Example 6 The difference between Comparative Example 6 and Example 2 is that Comparative Example 6 used triphenylmethyl hexafluorophosphate instead of (4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate. The experimental result showed no product because PF6... - Fluoride anion transfer is likely to occur, causing irreversible termination of carbocations.

[0100] Comparative Example 7 The difference between Comparative Example 7 and Example 2 is that Comparative Example 7 used triphenylmethyltetrafluoroborate instead of (4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate. No product was produced in Comparative Example 7 because of the presence of BF4 in the system. - Fluoride anion transfer is likely to occur, causing irreversible termination of carbocations.

[0101] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that titanium tetrachloride was used instead of dichloroethylaluminum as the co-initiator; all other parameters remained the same. The yield was 32%, and Mw = 31.2 × 10⁻⁶. 4 g / mol, Mn=12.4×10 4 The conversion rate is too low (g / mol), PDI = 2.52, and the molecular weight is also too low.

Claims

1. A method for the catalytic synthesis of high molecular weight polyisobutylene using a weakly coordinating anionic salt / alkyl aluminum composite system, characterized in that, Using isobutylene as the polymerization monomer, a composite initiation system consisting of a weakly coordinated anionic compound and alkyl aluminum was used to carry out cationic polymerization under low temperature conditions. After polymerization, the reaction was terminated, and high molecular weight polyisobutylene was obtained by precipitation, washing and drying. The weakly coordinating anionic compound is selected from organic anionic systems with weak nucleophilicity and low coordination ability. The weakly coordinating anion is selected from one or more of tetra(pentafluorophenyl)borate, tetra[3,5-bis(trifluoromethyl)phenyl]borate, perfluoroalkoxyaluminate, and their derived anions. The weakly coordinating anion is added to the polymerization system in the form of an iodonium salt, a caronium salt, or an organic salt capable of forming a stable carbocation. The iodonium salt is selected from one or more of diaryliodonium salt or iodonium salts containing a weakly coordinating anion. The caronium salt is selected from one or more of triphenylcaronium salt, tri(methylphenyl)caronium salt, or triarylcaronium salt containing a weakly coordinating anion. The organic salt capable of forming a stable carbocation is selected from one or more of N,N-dimethylaniline onionium salt, sodium tetra(pentafluorophenyl)borate, or sodium tetra[3,5-bis(trifluoromethyl)phenyl]borate. The alkyl aluminum is selected from one or more of dichloroethylaluminum, diethylaluminum chloride, diisobutylaluminum chloride, and dimethylaluminum chloride; wherein, the use of diethylaluminum chloride involves a mixture of at least two alkyl aluminums.

2. The catalytic synthesis method of high molecular weight polyisobutylene using a weakly coordinating anionic salt / alkyl aluminum composite system according to claim 1, characterized in that, Specifically, the following steps are included: S1: Material preparation: In an inert gas environment free from water and oxygen, the dehydrated and deoxygenated polymerization solvent, the dehydrated and deoxygenated isobutylene monomer, the weakly coordinated anionic compound, and the alkyl aluminum are all stored in an inert environment. S2: Aggregation: A weakly coordinating anionic compound was added to a low-temperature isothermal reactor to replace the reactor with an anhydrous and oxygen-free inert gas environment. A polymerization solvent and isobutylene monomer were added, and the temperature was equilibrated in the low-temperature isothermal reactor to obtain a polymerization system. Subsequently, alkyl aluminum was added to initiate a cationic polymerization reaction. After the polymerization was completed, a terminator was added to terminate the reaction and obtain a polymerization product solution. S3: Post-processing: After removing unreacted monomers and polymerization solvent from the polymerization product solution, it was washed and soaked with ethanol, and then dried to constant weight under vacuum drying conditions to obtain high molecular weight polyisobutylene.

3. The catalytic synthesis method of high molecular weight polyisobutylene using a weakly coordinating anionic salt / alkyl aluminum composite system according to claim 2, characterized in that, In S1, the solvent is selected from one or more of chloromethane, dichloromethane, n-hexane, toluene, chlorobenzene, and their mixtures.

4. The catalytic synthesis method of high molecular weight polyisobutylene using a weakly coordinating anionic salt / alkyl aluminum composite system according to claim 2, characterized in that, In S2, the molar ratio of the weakly coordinating anionic compound to the alkyl aluminum in the composite initiation system is 1:(10-100).

5. The catalytic synthesis method of high molecular weight polyisobutylene in a weakly coordinating anionic salt / alkyl aluminum composite system according to claim 2, characterized in that, In S2, the total concentration of the composite initiator system in the polymerization system is 10–100 mmol / L; the mass percentage concentration of isobutylene monomer in the polymerization system is 5 wt%–50 wt%.

6. The catalytic synthesis method of high molecular weight polyisobutylene in a weakly coordinated anionic salt / alkyl aluminum composite system according to claim 2, characterized in that, In the S2 process, the equilibrium temperature and time are 15-30 min, the polymerization temperature of the cationic polymerization reaction is -90 ℃ to -30 ℃, and the polymerization reaction time is 1-60 min.

7. The catalytic synthesis method of high molecular weight polyisobutylene in a weakly coordinating anionic salt / alkyl aluminum composite system according to claim 2, characterized in that, In S2, when there is only one type of alkyl aluminum, it is added to the polymerization system by slow dropwise addition at a rate of 0.5 to 2 mL / min; when there are two or more mixed alkyl aluminums, the alkyl aluminums are first mixed and then added to the initiation system at a rate of 0.5 to 2 mL / min.

8. The catalytic synthesis method of high molecular weight polyisobutylene in a weakly coordinating anionic salt / alkyl aluminum composite system according to claim 2, characterized in that, In step S2, the terminator is selected from water, anhydrous methanol, anhydrous ethanol, or an ethanol / water mixed solution containing 1 wt% NaOH; wherein the volume ratio of ethanol to water in the ethanol / water mixed solution is 1:1; and the amount of terminator used accounts for 1-5% of the total volume of the polymerization system. In S3, the method for removing unreacted monomers and polymerization solvent is vacuum evaporation; the ethanol soaking time is more than 12 hours; the vacuum drying process parameters are: absolute pressure of -0.1 MPa and drying temperature of 40-50 ℃.

9. A high molecular weight polyisobutylene, characterized in that, The high molecular weight polyisobutylene was prepared by a catalytic synthesis method using a weakly coordinating anionic salt / alkylaluminum composite system according to any one of claims 1 to 8, with a monomer conversion rate of 65% to 99%, and the weight-average molecular weight of the obtained high molecular weight polyisobutylene product ranged from 76.5 × 10⁻⁶. 4 ~157.9×10 4 g / mol, with a molecular weight distribution index of 1.99–5.

60.

10. The high molecular weight polyisobutylene according to claim 9, characterized in that, The following composite initiation system was used, in which the weakly coordinating anionic compound was (4-methylphenyl)(4-isopropylphenyl)iodonium tetra(pentafluorophenyl)borate, and the alkyl aluminum was a homogeneous mixture of diethylaluminum chloride and dichloroethylaluminum. The polymerization reaction was carried out at a polymerization temperature of -90 °C, with a monomer conversion rate of 92%. The weight-average molecular weight of the resulting polyisobutylene product was 157.9 × 10⁻⁶. 4 g / mol, with a molecular weight distribution index of 2.38.

Citation Information

Patent Citations

  • Process to prepare high reactive polyisobutene

    EP1344785A1